Simon and the holy night - Tharlet, Eve (Saxonville, Ma. : Picture Book Studio, 1991)
Relates how a little shepherd boy comes to witness the events surrounding the birth of Jesus Christ.
Keywords: Shepherds -- Fiction; Jesus Christ -- Nativity -- Fiction